Metabolic compensation of the Neurospora clock by a glucose-dependent feedback of the circadian repressor CSP1 on the core oscillator - Sancar, Gencer; Sancar, Cigdem; Brunner, Michael (Genes & development, 2012)
Conidial separation 1 (CSP1) is a global transcription repressor. It is expressed under control of the white collar complex (WCC), the core transcription factor of the circadian clock of Neurospora. Here we report that the length of the circadian period decreases with increasing glucose concentrations in csp1 mutant strains, while the period is compensated for changes in glucose concentration in wild-type strains. Glucose stimulated CSP1 expression. Overexpression of CSP1 caused period lengthening and, eventually, complete dampening of the clock rhythm. We show that CSP1 inhibits expression of the WHITE COLLAR 1 (WC1) subunit of the WCC by repressing the wc1 promoter. Glucose-dependent repression of wc1 transcription by CSP1 compensated for the enhanced translation of WC1 at high glucose levels, resulting in glucose-independent expression of the WCC and, hence, metabolic compensation that maintained a constant circadian period. Thus, the negative feedback of CSP1 on WC1 expression constitutes a molecular pathway that coordinates energy metabolism and the circadian clock.